2020
DOI: 10.3390/publications8040048
|View full text |Cite
|
Sign up to set email alerts
|

Digital Literacy and Higher Education during COVID-19 Lockdown: Spain, Italy, and Ecuador

Abstract: Digital literacy constitutes the basis for citizenship in order to be effective and efficient in the 21st Century in professional and personal lives. The set of skills and competences integrating digital literacy are expected to be guaranteed in higher education. During the lockdown globally imposed for the COVID-19 pandemic, educational systems worldwide had to face many disruptive changes. The aim of this research is to present a comparative study of three countries’ higher education institutions (Spain, Ita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
121
0
14

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 181 publications
(177 citation statements)
references
References 28 publications
2
121
0
14
Order By: Relevance
“…Teachers were found incompetent in designing interesting lesson and make available online for students to learn. This finding corroborates with research which reported that teachers did not have appropriate digitals kills to manage online classes (Tejedor et al, 2020). Similarly Heng and Sol (2020) pointed out that the success of online learning depends entirely on technological devices, the internet and the user.…”
Section: Discussionsupporting
confidence: 83%
“…Teachers were found incompetent in designing interesting lesson and make available online for students to learn. This finding corroborates with research which reported that teachers did not have appropriate digitals kills to manage online classes (Tejedor et al, 2020). Similarly Heng and Sol (2020) pointed out that the success of online learning depends entirely on technological devices, the internet and the user.…”
Section: Discussionsupporting
confidence: 83%
“…Just because their children are familiar with digital devices, many parents expect their children to be proficient enough to enroll in online or electronic learning, which often proves not to be the case (Akçayır, Dündar, & Akçayır, 2016;Kirschner & De Bruyckere, 2017;Nowak, 2019;Yong, Gates, & Harrison, 2016). In this sense, the situation brought about by the covid-19 pandemic has shown more clearly than ever students' lack of digital competence (Iivari, Sharma, & Ventä-Olkkonen, 2020;Tejedor, Cervi, Pérez-Escoda, & Jumbo, 2020).…”
Section: Covid-19 and E-learningmentioning
confidence: 99%
“…The other students, at all educational levels, were mostly assigned tasks to complete at home, and no inperson exams were allowed, due to the above-mentioned lockdown (Area-Moreira, Bethencourt-Aguilar, Martín-Gómez, & San Nicolás-Santos, 2020). Although this situation fostered students' autonomous learning and their digital competences increased (Gonzalez et al, 2020) it was evident that students and teachers were not provided with the necessary electronic resources and online tools due to the fast improvisation made necessary by the sudden lockdown (Ramos-Morcillo, Leal-Costa, Moral-García, & Ruzafa-Martínez, 2020;Tejedor et al, 2020).…”
Section: The Educational Organization Due To Covid-19 In Spainmentioning
confidence: 99%
“…This transformation of the education system is the response needed to meet two significant demands: The need to adapt to a global world and the evolution of a knowledge society [9]. Today, a third demand has been added, the need to adapt to a global pandemic context [10,11]. In fact, the emergence of new technologies has already introduced novel approaches to education: New training modalities (such as e-learning and blended learning) and mass education (such as mass and open online courses-MOOC); new ways for collaborative learning among students (WebQuest, project-based learning); improvement in the acquisition of skills with access to large amounts of information; changes in the roles of teachers and students; methodological changes (flipped classroom), etc., [12].…”
Section: Introductionmentioning
confidence: 99%